PREVALENCE OF WEST NILE VIRUS ANTIBODIES IN INDOOR DOGS FROM AN URBAN AREA IN IAȘI, ROMANIA: INDICATORS OF VIRAL PRESENCE AND URBAN TRANSMISSION POTENTIAL - Luanda Elena OȘLOBANU; Luciana Alexandra CRIVEI; Ioana Alexandra RĂȚOI; Ioana Cristina CRIVEI; Gheorghe SAVUȚA (Journal of Applied Life Sciences and Environment, 2023)
West Nile Virus (WNV), a zoonotic mosquito-borne virus (mobovirus) originally isolated from the blood of a febrile Ugandan woman in 1937, caused substantial human disease in Europe starting in the 1990s and emerged in 1999 in The United States of America (USA) for the first time. It has become an important concern for public health due to its reemergence and frequent human outbreaks. The enzootic transmission cycle of arboviruses involves primary wild animals; however, spillover transmission is reported frequently in domestic animals. Dogs are dead-end hosts in WNV transmission epidemiology. However, detecting WNV antibodies in the dog population can indicate the virus’s presence and spread in different areas. The virus is known to be endemic in parts of Romania, including Iași County. The study aimed at assessing the prevalence of anti-WNV antibodies in indoor dogs from an urban area in Iași, where all the conditions for virus transmission are met (wetland, density of wildlife hosts including birds, abundance of vectors, domestic mammal hosts and synanthropic birds). Using a commercial enzyme-linked immunosorbent assay (INGEZIM West Nile COMPAC, Ingenasa, Madrid, Spain), serum samples collected from indoor dogs between 2020–2022 were screened for WNV antibodies. The results showed an overall seroprevalence of 12.2%. Detection of specific antibodies in dogs suggests a possible establishment of an urban cycle for WNV or other antigenically related flaviviruses.